2022
DOI: 10.1038/s41396-022-01296-7
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome of the freshwater sponge Ephydatia muelleri shares compositional and functional similarities with those of marine sponges

Abstract: Sponges are known for hosting diverse communities of microbial symbionts, but despite persistent interest in the sponge microbiome, most research has targeted marine sponges; freshwater sponges have been the focus of less than a dozen studies. Here, we used 16 S rRNA gene amplicon sequencing and shotgun metagenomics to characterize the microbiome of the freshwater sponge Ephydatia muelleri and identify potential indicators of sponge-microbe mutualism. Using samples collected from the Sooke, Nanaimo, and Cowich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 76 publications
2
18
1
Order By: Relevance
“…In terms of composition, t 2 to t 4 samples are highlighted by a high abundance of Gammaproteobacteria, with three dominant families: Comamonadaceae, Alteromonadaceae and Pseudomonadaceae. These families are commonly occurring in freshwater sponges [21,31,60] and might be related to chemical defenses [61]. For example, Comamonadaceae were associated with defense mechanisms such as CRISPR and intracellular tra cking within E. muelleri [31], while diverse PKS genes were found within Pseudomonadaceae and Alteromonadaceae (dominant genus: Rheinheimera) associated with the freshwater sponges Rezinkovia echinata (Lake Baikal) and E. uviatilis (Vinkeveense Plassen, the Netherlands), respectively [62,63].…”
Section: Links Between the Ontogeny Of S Lacustris Juveniles And The ...mentioning
confidence: 99%
See 3 more Smart Citations
“…In terms of composition, t 2 to t 4 samples are highlighted by a high abundance of Gammaproteobacteria, with three dominant families: Comamonadaceae, Alteromonadaceae and Pseudomonadaceae. These families are commonly occurring in freshwater sponges [21,31,60] and might be related to chemical defenses [61]. For example, Comamonadaceae were associated with defense mechanisms such as CRISPR and intracellular tra cking within E. muelleri [31], while diverse PKS genes were found within Pseudomonadaceae and Alteromonadaceae (dominant genus: Rheinheimera) associated with the freshwater sponges Rezinkovia echinata (Lake Baikal) and E. uviatilis (Vinkeveense Plassen, the Netherlands), respectively [62,63].…”
Section: Links Between the Ontogeny Of S Lacustris Juveniles And The ...mentioning
confidence: 99%
“…These families are commonly occurring in freshwater sponges [21,31,60] and might be related to chemical defenses [61]. For example, Comamonadaceae were associated with defense mechanisms such as CRISPR and intracellular tra cking within E. muelleri [31], while diverse PKS genes were found within Pseudomonadaceae and Alteromonadaceae (dominant genus: Rheinheimera) associated with the freshwater sponges Rezinkovia echinata (Lake Baikal) and E. uviatilis (Vinkeveense Plassen, the Netherlands), respectively [62,63]. This speci c bacterial community acquired during the formation of the aquiferous system and the rst lter-feeding activity steps could be linked to the early development of bacterial symbionts acting for the chemical defense of the sponge.…”
Section: Links Between the Ontogeny Of S Lacustris Juveniles And The ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Sugden et al [2] reported for the first time the comparison between spongeassociated communities and the surrounding environments (e.g., water and biofilm). This latter aspect is of major importance to establish if discrepancies between prokaryotic communities in sponges and water can match the differences that may be observed between benthic and planktonic communities rather than the functional significance of host-microbe specificity [2]. The sponge immune system constitutes a first line of defense against transient microbiota, including the production of biomolecules that recognize conserved microbial structures [24].…”
Section: Introductionmentioning
confidence: 99%